Cadastro territorial multifinalitário na elaboração da planta genérica de valores do município de Cubatão/SP - Medeiros, Raphael Duarte (Universidade Federal de São Carlos, 2023)
The aggravation of the financial crisis in recent decades has highlighted the dependence of municipalities on the Union. The decrease in revenue makes Mayors and Secretaries seek new methods to balance income and expenses. In this scenario, the use of the Multipurpose Technical Cadastres (MTC) emerges as a powerful tool for territorial organization, assisting municipal managers in decision-making. Despite its effectiveness, the high cost of such tools and the low level of specialization of the operational layer of the municipalities sometimes impedes the use of technological tools such as CTM. With the creation of the Program for Modernization of Municipal Tax Administrations (PMAT) and the popularization of Geoprocessing techniques, small and medium-sized municipalities have an unprecedented opportunity to use resources to build and/or optimize the CTM, balance their revenue, and reduce dependence on Union transfers. This study aims to propose a methodology and use CTM to create Generic Value Plants.
Multipurpose technical cadastres in the in the development of generic property valuation map of the municipality of Cubatão/SP
Keywords: Cadastro Territorial Multifinalitário; IPTU; Planta genérica de valores; Multipurpose technical cadastres; Property tax; Generic value plants; ENGENHARIAS; CIENCIAS SOCIAIS APLICADAS::PLANEJAMENTO URBANO E REGIONAL::METODOS E TECNICAS DO PLANEJAMENTO URBANO E REGIONAL